Novel Antibiotic Combinations of Diverse Subclasses for Effective Suppression of Extensively Drug-Resistant Methicillin-Resistant Staphylococcus aureus (MRSA) - Shumyila Nasir; Muhammad Sufyan Vohra; Danish Gul; Umm E Swaiba; Maira Aleem; Khalid Mehmood; Saadia Andleeb (International Journal of Microbiology)
The emergence of multidrug-resistant pathogens such as methicillin-resistant Staphylococcus aureus (MRSA), the chief etiological agent for a range of refractory infections, has rendered all β-lactams ineffective against it. The treatment process is further complicated with the development of resistance to glycopeptides, primary antibiotics for treatment of MRSA. Antibiotic combination therapy with existing antimicrobial agents may provide an immediate treatment option. Minimum inhibitory concentrations (MICs) of 18 different commercially available antibiotics were determined along with their 90 possible pairwise combinations and 64 triple combinations to filter out 5 best combinations. Time-Kill kinetics of these combinations were then analyzed to find collateral bactericidal combinations which were then tested on other randomly selected MRSA isolates. Among the top 5 combinations including levofloxacin-ceftazidime; amoxicillin/clavulanic acid-tobramycin; amoxicillin/clavulanic acid-cephradine; amoxicillin/clavulanic acid-ofloxacin; and piperacillin/tazobactam-tobramycin, three combinations were found to be collaterally effective. Levofloxacin-ceftazidime acted synergistically in 80% of the tested clinical MRSA isolates. First-line β-lactams of lower generations can be used effectively against MRSA infection when used in combination. Antibiotics other than glycopeptides may still work in combination.